PENDIDIKAN RUMAH TANGGA MENURUT ABDULHAMID ABUSULAYMAN - Nabil, Amir Ahmad (Al-Iqro', 2025)
The paper aims to highlight AbdulHamid AbuSulayman’s (1936-2021) epistemological outlook of Islamic education especially in the context of religious and spiritual instruction relating to familial matters and relation. It aspires to understand the issue from contextual interpretation of the meaning of the ayah as alluded to by the practice of the salaf and the spirit of the shariah. The study is based on qualitative method by way of literature survey and content analysis. The data was analyzed using hermeneutical and philosophical approaches of Abdullah Saeed and Fazlur Rahman’s contextual and double movement framework. The finding shows critical epistemological and structural reform introduced by AbdulHamid AbuSulayman in his works on marital discord and the inviolable principle of human dignity as enshrined in the doctrines of the higher objectives of Islamic Law that presents comprehensive and coherent interpretation of the Qur’an and hadith that celebrates the dynamic context and ideal of shariah to safeguard the welfare of women and children, and transcendental humanistic and reciprocal value and uphold their right and responsibility as guaranteed by law and its manifestation in contemporary legal verdict and opinion showing sympathetic voice on their favour. It contributed to strategic educational breakthrough that uplift their untapped voice and aspiration.